Selection of Cellulolytic Bacteria Found in Mask Waste from Wana Tirta Mangrove - Pramesti, Ariska Hanum; Octavia, Bernadetta (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2025)
The amount of mask waste has increased significantly due to the COVID-19 pandemic. Mask waste can be found everywhere, likewise in Wana Tirta Mangrove. Its existence in the mangrove ecosystem, making mask waste, has the potential for cellulolytic bacteria. The purpose of this study is to determine the cellulase enzyme activity, characteristics, and genus of purified cellulolytic bacteria found in mask waste from Wana Tirta Mangrove. The method used in this study was qualitative research. The samples for this research were bacterial isolates from mask waste, which had previously been isolated from the Wana Tirta Mangrove. Samples were grown on CMC media to determine isolates that were included in cellulolytic bacteria. The cellulase activity of cellulolytic bacteria was tested qualitatively and quantitatively. Morphological, physiological and biochemical tests were carried out to obtain phenetic characters which were then used as the basis for determining the genus of cellulolytic bacteria. The results showed that 10 isolates were cellulolytic bacteria. The highest activity of cellulase enzyme qualitatively was produced by isolate 72 with a value of 0.466 mm, while the highest activity of cellulase enzyme quantitatively was produced by isolate 84 with a value of 0.931 U/ml. The dendrogram result showed 4 genera of cellulolytic bacteria, including Pseudomonas, Alcaligenes, Cellulomonas, and Aeromonas.